Teaching of health-related physical activity in medical schools: the Brazilian scenario - Adriana Akemi Dourado; Pedro Rodrigues Curi Hallal; Marlos Rodrigues Domingues; Fernando Vinholes Siqueira (Revista Brasileira de Atividade Física e Saúde)
Physical activity engagement is a key strategy to improve population health and quality of life. However, studies show that physical activity counseling by physicians is low, and one of the main barriers reported is lack of specific knowledge. The aim of this study is to describe the existence of health-related physical activity content in the curricula of Brazilian Medicine undergraduate courses. A census-type descriptive study was carried out. Online documentation available in institutional websites of all Brazilian Medicine courses curricula were assessed and, when not available, faculty members were contacted. In 2015 we identified 233 medicine courses in Brazil, using data from the Brazilian Ministry of Education. We assessed the documentation in detail of 158 courses (67.8%). We observed that only 12% of curricula presented health-related physical activity and/or physical exercise contents. This proportion was higher in public Medical schools compared to private ones (21.5% vs. 5.4%; p = 0.002). Teaching of health-related physical activity in Brazilian Medicine courses is scarce. We highlight the need for adjustment of curricula considering the well-established benefits of physical activity for public health.